Repetitive transcranial magnetic stimulation for patients with functional paralysis: a randomized controlled study. (14th February 2022) - Chastan, Nathalie; Etard, Olivier; Parain, Dominique; Gerardin, Priscille; Fouldrin, Gaël; Derambure, Philippe; Tard, Céline; Gillibert, André; Nathou, Clément; Delval, Arnaud; Welter, Marie‐Laure; Guillin, Olivier
Abstract: Background and purpose: Repetitive transcranial magnetic stimulation (rTMS) has been proposed to treat functional neurological disorders. Here, the aim was to assess the efficacy of rTMS to treat functional paralysis in a controlled randomized trial. Methods: Patients received two sessions of active or sham 0.25 Hz rTMS (60 stimuli each), with a 1‐day interval, applied over the motor cortex contralateral to the paralysis. The primary outcome was the number of patients with an increase in motor score between baseline and after the second rTMS session, rated by two investigators blinded to the treatment allocation. Secondary outcomes were changes in global and fine motor scores between groups after rTMS, and the occurrence of adverse events. Results: Sixty‐two patients (46 female; mean [SD] age, 35.2 [13.9] years) were enrolled and randomized. Thirteen out of 32 (41%) and 11/30 (37%) patients had increased motor strength after active or sham rTMS, respectively ( p  = 0.80). Changes in both global and fine motor scores after rTMS relative to baseline were also not significantly different between treatment groups (median difference in the global motor score 0.62 [0.83] and 0.37 [0.61], and in the fine motor scores 0.12 [0.18] and 0.08 [0.11], in active and sham rTMS groups, respectively; p  = 0.14). Six serious adverse events, consisting of three cephalalgia in the active group and two cephalalgia and one asthenia in the sham group, were observed. Conclusions: Two sessions of sham or active low frequency rTMS were effective to improve functional paralysis, suggesting a placebo effect of this non‐invasive brain stimulation technique. Abstract : The efficacy of sham or active rTMS to treat functional paralysis was assessed in a controlled randomized trial. Sixty‐two patients received two sessions of active or sham 0.25 Hz rTMS (60 stimuli each), with a 1‐day interval, applied over the motor cortex contralateral to the paralysis. Two sessions of sham or active low frequency rTMS were found to be effective to improve functional paralysis, suggesting a placebo effect of this non‐invasive brain stimulation technique.